The complementary roles of STAT3 and STAT1 in cancer biology: insights into tumor pathogenesis and therapeutic strategies - Wang, Weiyuan; Lopez McDonald, Melanie Cristina; Kim, Christine; Ma, Mirielle; Pan, Zetao (Tommy); Kaufmann, Charlotte; Frank, David A. (Frontiers in Immunology, 2023)
STATs are a family of transcription factors that regulate many critical cellular processes such as proliferation, apoptosis, and differentiation. Dysregulation of STATs is frequently observed in tumors and can directly drive cancer pathogenesis. STAT1 and STAT3 are generally viewed as mediating opposite roles in cancer development, with STAT1 suppressing tumorigenesis and STAT3 promoting oncogenesis. In this review, we investigate the specific roles of STAT1 and STAT3 in normal physiology and cancer biology, explore their interactions with each other, and offer insights into therapeutic strategies through modulating their transcriptional activity.